Estimation Parameter d in Autoregressive Fractionally Integrated Moving Average Model in Predicting Wind Speed - Devi Ila Octaviyani; Madona Yunita Wijaya; Nina Fitriyati (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2019)
AbstractWind speed is one of the most important weather factors in the landing and takeoff process of airplane because it can affect the airplane's lift. Therefore, we need a model to predict the wind speed in an area. In this research, the wind speed forecast using the ARIMA model is discussed which has differencing parameters in the form of fractions. This model is called the ARFIMA model. In estimating differencing parameters two methods are considered, namely parametric and semiparametric methods. Exact Maximum Likelihood (EML) is used under parametric method. Meanwhile, four methods semiparametric estmation are used, i.e Geweke and Porter-Hudak (GPH), Smooth GPH (Sperio), Local Whittle and Rescale Range (R/S). The result shows the best estimation method is GPH with the selected model is ARFIMA (2,0.334,0).Keywords: ARFIMA, Parametric Method, Semiparametric Method. AbstrakKecepatan angin merupakan salah satu faktor cuaca yang penting dalam proses pendaratan dan tinggal landas pesawat karena dapat mempengaruhi daya angkat pesawat. Oleh karena itu, diperlukan suatu model untuk memprakirakan kecepatan angin di suatu wilayah. Artikel ini membahas prakiraan kecepatan angin dengan menggunakan model ARIMA yang memiliki parameter differencing berupa bilangan pecahan. Model ini disebut model ARFIMA. Pada estimasi parameter differencing terdapat dua metode yang digunakan pada penelitian ini, yaitu metode parametrik dan metode semiparametrik. Metode parametrik yang digunakan adalah Exact Maximum Likelihood (EML) dan empat metode semiparametrik yang digunakan adalah Geweke and Porter-Hudak (GPH), Smooth GPH (Sperio), Local Whittle dan Rescale Range (R/S). Hasil analisis menunjukkan pada kasus ini metode estimasi terbaik adalah GPH dengan model terpilih adalah ARFIMA(2,0.334,0).Kata kunci: ARFIMA, Metode Parametrik, Metode Semiparametrik.